2014
DOI: 10.1080/00220272.2014.883553
|View full text |Cite
|
Sign up to set email alerts
|

Marketized private tutoring as a supplement to regular schooling: Liberal Studies and the shadow sector in Hong Kong secondary education

Abstract: Around the world, increasing numbers of students receive after-school private supplementary tutoring. Such tutoring may be provided through informal channels or by companies, and it may be received one-to-one, in small groups or in large classes. The tutoring is commonly called shadow education since its content mimics that of regular schooling. The spread of shadow education is part of a global shift of balance with increased roles for the private sector. Hong Kong is among the societies in which shadow educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 31 publications
2
47
0
2
Order By: Relevance
“…Such texturing is important for understanding that not all actors behave in the same way. Chan and Bray (2014) made this point when looking at why students sought tutoring in one particular subject (Liberal Studies) in Hong Kong. In this article, we used a wider lens to elaborate on this understanding.…”
Section: Ecological Understanding and Beyondmentioning
confidence: 98%
See 1 more Smart Citation
“…Such texturing is important for understanding that not all actors behave in the same way. Chan and Bray (2014) made this point when looking at why students sought tutoring in one particular subject (Liberal Studies) in Hong Kong. In this article, we used a wider lens to elaborate on this understanding.…”
Section: Ecological Understanding and Beyondmentioning
confidence: 98%
“…Evolving ecosystems in education: The nature and implications… and Bray 2014;Yung 2015). Some scholars have assessed the scale of tutoring quantitatively using questionnaires (e.g., Safarzyńska 2013;Zhang 2013).…”
Section: Private Supplementary Tutoringmentioning
confidence: 99%
“…One recent study, for example, revealed that 16 students from the same school and cohort attending tutorial centres for a subject called Liberal Studies were doing so because of different ''push'' factors. 8 As for the ''pull'' factors, the study found that tutorial centres knew how to meet the social, learning and psychological needs of their student clienteles (Chan and Bray 2014). While it is easy to view the ''pull'' factors as marketing strategies of tutorial centres (after all they operate in a profiteering enterprise), it is not easy to dismiss students' prevalent perception that attending tutorial centres had improved their learning, as research evidence has suggested (see for example Bray 2013 andZhan et al 2013).…”
Section: Preliminary Fieldworkmentioning
confidence: 99%
“…I argue that tutorial centre advertisements provoke students' feelings of insecurity and their fears that they might not do well in the Hong Kong Diploma in Secondary Education (HKDSE), compelling them to turn to tutorial classes as safety support to increase their chance of success. 4 Indeed, the media marketing of tutorial centre advertisements produces a register of emotions, ranging from inadequacy to fear, which is what tutorial centres capitalise on to enlarge their market (Chan and Bray 2014).…”
Section: Emotion Studiesmentioning
confidence: 99%
“…Research has shown that shadow education has grown in popularity in recent decades and that there is a "prodigious growth in out-of-school, private educational activities meant to supplement formal schooling is observed worldwide" (Mori & Baker, 2010). Shadow education has been extensive in East Asia, but in recent decades it has acquired worldwide dimensions (Chan & Bray, 2014). Similarly, research in England indicates that about 25% of students have attended private tuition during primary or secondary education (Ireson & Rushforth, 2005), while resort to private tuition is extremely common in Greece, especially in relation to preparing university applicants for the highly competitive university entrance examinations.…”
Section: Introductionmentioning
confidence: 99%